Preliminary Study in Overview of CYP2A6 Gene Variation in Infertile Male Patients - Jihadin Rasyadi Mumtaz; Zeti Harriyati; Chris Adhiyanto; Nurul Hiedayati; Yona Mimanda; Muniroh Muniroh (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2021)
Introduction: Infertility is a condition which is described by WHO as inability for having children after one year of relationship without birth control. this condition can be caused both from inside and outside the body. One of the major outside factors is exposure to chemical substances, which in this case nicotine substance that came from cigarettes. The CYP2A6 gene is a coding gene for the xenobiotic metabolic enzyme, in this case nicotine which can cause infertility in men. Mutations in this gene can lead to nicotine buildup, increasing nicotine effect thus increasing the risk of infertility in men. The aim of this study was to determine whether there were variations in the CYP2A6 gene in male infertile patients.Methods: The method used was the isolation of infertile and fertile sperm DNA samples (five samples each) which were then amplified at the target DNA (CYP2A6) by PCR method and then sequenced to see the nucleutide sequence.Result: The results of this study showed that there were variations in the CYP2A6 gene that occurred only in infertile patients, heterogeneous mutations in the 7788th(C-A), 8040th (C-T), 7661st (G-C) nucleutide sequence of the CYP2A6 gene and SNP mutations in the 8250th(T>C), 8409th (T>G/C), and 8428th(C>T) nucleutide sequence of the CYP2A6 gene.Conclusion: The conclusion of this study is that there are CYP2A6 variations that found only in infertile male patients.